RESILIENCE, SELF-EFFICACY AND MOTIVATION AS POSITIVE PSYCHOLOGICAL CHARACTERISTICS OF STUDENT AND PROFESSIONAL DANCERS - Tatyanne Roiek Lazier Leão; Luciana Ferreira; Cleber Mena Leão Junior; José Luiz Lopes Vieira (Journal of Physical Education)
ABSTRACT This study aimed at assessing the following psychological variables: resilience, self-efficacy and motivation. A total of 135 dancers participated in the study, that is, 112 students from the Brazilian dance school known as Escola de Dança do Teatro Guaíra, 15 professional dancers from the school referred to as Balé Teatro Guaíra, and 08 professional dancers from the school named G2 Cia de Dança. The evaluation of the psychological variables was carried out by using four questionnaires: Resilience Scale (RS), General Self-Efficacy Scale (GSE), Self-Efficacy Scale for Dancers (SESD), and Sport Motivation Scale-II (SMS-II). The Hierarchical Cluster Analysis with the Ward's method and Mann-Whitney test were used for assessing the data. The results showed that students and professionals have similar levels of motivation, but divergent ones regarding friendship, personal fulfilment, satisfaction, meaning of life and self-confidence, ability to adapt to situations of resilience, and psychological self-efficacy. The Cluster Analysis enabled the researchers to organize the group of student dancers with similar characteristics into three clusters, that is, ‘predominant’, ‘intermediate’ and ‘minority’, whereas the group of professional dancers was divided into two groups, ‘minor and ‘major’’. It was concluded that both student dancers and professional ones showed high values of resilience, self-efficacy and motivation. These results highlight that dance has an important role in the construction of a positive psychological profile.